AKIBAT HUKUM KEPAILITAN SUAMI TERHADAP HARTA BERSAMA MENURUT UNDANG-UNDANG KEPAILITAN (Analisis Putusan Mahkamah Agung Nomor: 057.PK/Pdt.Sus/2010) - Sebayang, Siddik Meliasta (Universitas Muhammadiyah Sumatera Utara, 2017)
Marital property is the property acquired during the marriage, regardless of who produced it (either husband or wife only, or husband and wife), then the property belongs to both and the marital property. Concerning the marital property of a husband or wife may act solely on mutual consent or consent of both parties. The existence of wealth in marriage is not only the possibility of property owned by each husband and wife. This study is a descriptive analysis that leads to normative juridical research. Based on the results of the study found that the marital status of husband or wife to marital property is same. The legal provisions concerning the payment of the debt of a spouse or husband for the settlement of the debt concerned shall be repayable on the goods of origin of the husband or the wife who holds the debt, unless the marriage agreement is made before it is executed. The consequences of the bankruptcy law of husbands against joint property can be applied as a joint bankruptcy because basically the unity of property is not only the merging of wealth but also the burden of payment. Bankruptcy husband and wife who married in unity of property, treated as bankruptcy unity of property. Settlement of bankruptcy dispute can be done through the mechanism of bankruptcy application and also through the mechanism of postponement of debt payment obligation in accordance with the rules of the applicable legislation.